The risk of sudden death in sport in patients with signs of connective tissue dysplasia (literature review) - Nekhanevych O.B.; Abramov V.V. (Medičnì Perspektivi)
Literature review indicates that, despite the disclosure of a number of causes and mechanisms of sudden death in people performing physical activities, this issue remains relevant today. The main cause of sudden death in sport is pathological conditions and heart diseases. Par¬ticular risk group during follow-up over persons involved in physical activity are those with the presence of small anomalies; this may be a ma¬nifestation of connective tissue dysplasia. With all the variety of affected organs and systems in patients with connective tissue dysplasia, cardio¬vascular disorders are the leading pathology determining the quality and pro¬gnosis of life.